A study of solidification on binary eutectic system with moving phase change material - Chaurasiya V.; Rai K.N.; Singh J. (My University, 2025)
A one-dimensional moving boundary problem describing solidification of a eutectic system under imposed material movement occupying a semi-infinite medium is solved for two different cases of solid fraction distribution within the mushy zone. In the first case it is assumed that the solid fraction distribution has a linear relationship with temperature and in the second case solid fraction distribution is varying linearly with distance within the mushy zone. An exact solution of the problem is obtained with the help of a similarity technique. To demonstrate the current study experimental data of Al-Cu solidification are presented. All the thermal-physical properties of each part are discussed in detail for both models. The temperature profile in each region and moving interfaces are calculated for different Peclet number Pe. In the present study it is shown that the moving interfaces are enhanced, growing relatively faster and assisting in the process of phase-transition when material moves in the direction of freeze but transition is delayed when material moves in the reverse direction. It is also shown that mushy zone becomes thinner when surface temperature is lower than the solidus temperature for different Peclet numbers. In addition, the heat removal Q at the surface ξ=0 is shown with respect to time for different Peclet numbers. To validate our study, we compare our results with a previous published work and they are found to be close. © 2021 Elsevier Ltd